2007
DOI: 10.1197/jamia.m2255
|View full text |Cite
|
Sign up to set email alerts
|

Informatics Systems to Promote Improved Care for Chronic Illness: A Literature Review

Abstract: In all, 109 articles were reviewed involving 112 information system descriptions. Chronic diseases targeted included diabetes (42.9% of reviewed articles), heart disease (36.6%), and mental illness (23.2%), among others. System users were primarily physicians, nurses, and patients. Sixty-seven percent of reviewed experiments had positive outcomes; 94% of uncontrolled, observational studies claimed positive results. Components closely correlated with positive experimental results were connection to an electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
149
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(157 citation statements)
references
References 40 publications
5
149
0
3
Order By: Relevance
“…Nonclinical staff members benefited both from new access to patient information, which they found useful, and from new information management tools, which made the information easier to use. Our study supports others [17][18][19][20] demonstrating that when the specific needs of users are met, usefulness and use is high, although these dimensions varied in our study according to provider type and work setting. The work of medical providers and case managers often resemble putting together the puzzle that is the patient case.…”
Section: Discussionsupporting
confidence: 90%
“…Nonclinical staff members benefited both from new access to patient information, which they found useful, and from new information management tools, which made the information easier to use. Our study supports others [17][18][19][20] demonstrating that when the specific needs of users are met, usefulness and use is high, although these dimensions varied in our study according to provider type and work setting. The work of medical providers and case managers often resemble putting together the puzzle that is the patient case.…”
Section: Discussionsupporting
confidence: 90%
“…A study of care coordination programs in Medicare found that only one of fifteen programs experienced lower hospitalizations after the program although there were modest improvements in quality. 15 A review of studies found that population management had a positive impact on care processes and outcomes, 16 so reasons for the significant association of higher population management score and risk for avoidable hospitalizations in our population is unclear. It may be that a greater degree of population management enabled higher-risk individuals to be identified and hospitalized.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research demonstrated that such systems can be feasible, secure, and well accepted by patients. 6,7,9,11,13,[15][16][17] Laboratory results and e-mail typically have been the most popular features.Fewer systems have been developed specifically for pediatrics. General pediatrics has lagged behind other specialties in uptake of electronic health tools.…”
mentioning
confidence: 99%